Using insulin clamp technique as part of the perioperative care - Mazen Hassanain (Wolters Kluwer Medknow Publications, 2019)
Operatively induced inflammation has been the focus of many studies to evaluate the most efficient responses and protocols to be used for its control. Insulin has been characterized with nonmetabolic properties and is used as a preoperative anti-inflammatory agent. We reviewed the published evidence in the past 10 years reporting on the use of glucose-insulin-normoglycemia therapy as a potential anti-inflammatory therapy to improve surgical outcomes about tissue trauma, with the challenges and progress attenuated so far. We also portray our experience in the use of insulin therapy on our liver resection patients as well as the significant knowledge gaps that still exist and the need for a multidisciplinary approach to bridge them.